Development and in vitro skin delivery of dexamethasone acetate-loaded surfactant-based systems - Urban, Maria Cristina Cocenza; Landgraf, Daniele S; Oyafuso, Marcia Helena; Chiavacci, Leila Aparecida; Sarmento, Victor Hugo Vitorino; Chorilli, Marlus [UNESP]; Corrêa, Marcos Antonio; Gremião, Maria Palmira Daflon [UNESP] (American Scientific Publishers, 2013)
Topical corticosteroids, e.g., dexamethasone acetate (DMA), are extensively used to treat cutaneous inflammatory disorders even though their use is correlated with potential local and systemic side effects. The objective of this study was to develop and test the topical delivery of DMA-loaded surfactant based systems in vitro; these studies could guarantee a suitable delivery and therapeutic efficacy, as well as minimize DMA's side effects. A phase diagram was constructed using polyoxypropylene (5) polyoxyethylene (20) cetyl alcohol as the surfactant (S), isopropyl myristate as the oil phase (O) and water (W). The systems were characterized using polarization light microscopy (PLM), as well as rheological and small angle X-ray scattering (SAXS) measurements. Depending on the concentration of the constituents, it was possible to obtain microemulsions (MEs) and liquid crystalline mesophases (lamellar and hexagonal). These types of arrangement were verified using PLM measurements. The SAXS results revealed that increasing the W/S ratio led to ME, as well as lamellar (LAM) and hexagonal (HEX) arrangements. The MEs displayed typical Newtonian behavior while the LAM and HEX phases exhibited pseudoplasticity and plasticity, respectively. The MEs displayed excellent drug solubilization that was approximately 10-fold higher than was observed with the individual components. The in vitro cutaneous permeation studies using pig ear skin and analysis of the mechanical parameters (hardness, compressibility, cohesiveness and adhesiveness) were carried out with a HEX phase and O/W emulsion. The HEX phase achieved better drug permeation and retention in the skin while its mechanical properties were suitable for skin administration. PPG-5-CETETH-20-based systems may be a promising platform delivering DMA and other topical corticosteroids through the skin.